15.2k views
4 votes
Write a formula for f(a) in terms of a -3a + 6b = a + 4b

Write a formula for f(a) in terms of a -3a + 6b = a + 4b-example-1

2 Answers

1 vote

Answer:

Step-by-step explanation: Answer: 2a

Trust ;)

User Edward Strange
by
6.8k points
5 votes

Answer:


\huge\boxed{\sf f(a) = 2a}

Explanation:

-3a + 6b = a + 4b

Isolate b

6b - 4b = a + 3a

2b = 4a

b = 4a / 2

b = 2a

Replace b by f(a)

f(a) = 2a


\rule[225]{225}{2}

Hope this helped!

~AH1807

User Morena
by
7.2k points